The Impact Of Omnichannel Experience And Brand Image On Consumer Purchase Intentions Mediated By Consumer Attitudes - Shinta Rahmani; Ervan Susilowati; Femmy Effendy (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This research investigates the nuanced relationships among omnichannel experiences, brand image, consumer attitudes, and purchasing behavior within the beauty and wellness industry, focusing on PT. Mustika Ratu, Tbk. The study employs a random sampling technique, surveying 60 individuals to gather insights. The direct test results indicate significant direct relationships between omnichannel experiences, brand image, and both consumer attitudes and purchasing intentions. Moreover, the indirect paths highlight the pivotal mediating role of consumer attitudes in translating the impacts of omnichannel experiences and brand image into actual consumer purchases. These findings provide actionable insights for PT. Mustika Ratu, emphasizing the need to strategically cultivate positive consumer attitudes alongside optimizing omnichannel experiences and enhancing brand image to effectively drive purchasing behavior in the competitive beauty and wellness sector.